Refrain and Hesitation of EFL Students in Class Oral Participation: Problems and Solutions - Dalaf, Muna (Al-Adab Journal, 2019)
One of the biggest barriers for the teachers is the low participation of his students. Students’ low participation is a big hurdle that lowers the teachers’ enthusiasm. This matter can be really devastating to the teachers who feel helpless in such situations. The non-participation happens due to different factors. Thus, it seems that the teacher’s mission is a very difficult one. He must be an influential role model when he deals with his students. One of the influential ideas that increase students’ participation is to bring technology to the classroom. The researcher noticed that shy students felt more confident when their attention is shifted from being toward the class into being towards the program and its interesting presentations. As a result this research is going to explore the problem of student non-participation at Al-Mustansiriyah University and the effect of using technology to increase their participation.